Dragon in Partnership's Clothing. About European - Asian Cooperation - Example of China and Spain - Grzywna, Agnieszka (Smok w owczej skórze. O współpracy europejsko-azjatyckiej na przykładzie Chin i Hiszpanii, 2010)
The relationship that exists between Asia and Europe has always been important for both sides. As a result of the great development of the Orient, these countries have begun to be more and more important for international relations. The process of the industrialization of Asian economies was possible thanks to some countries like Japan, China, Hong Kong, Singapore or India which have gradually become new "giants". By taking China and Spain as representatives of European Union and Asian cooperation, an important image of the present and future situation will be created. The background of China's peaceful rise will come under close scrutiny, as well as the origins of foreign investments. At present China is trying to implement the politics of the United States of America that consist of "dividing and ruling" and is directing it towards the EU.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 197-210
Keywords: cooperation; Asia; Europe; bilateral trade; partnership